DEVELOPMENT OE EQUATION TO PREDICT THE MINIMAL W R E S T L I N G W E I G H T O F Y O U N G (11-13 Y E A R S O F A G E ) TURKISH WRESTLERS - Kutlu, Mehme (Gazi Üniversitesi, 1996)
[EN] The purpose of this study was to develop to predict minimal wrestling weight of the small Turkish wrestlers who has to arrange their weight in a healthy way. The subject of this study were 169 prepubescent wrestlers. They had choosen by the Turkish Wrestling Federation to bi placed at the wrestling schools. Following measurements of all subjects were taken; under water weighting, anthropometric diameter measurements and vital capacity measurement. The equations to predict minimal weight was obtained through multiple linear Regression statisticalmethod,where real minimal weight with 5 (7c minimal fat determined throi weighting was dependent variable New equations for pn follows.MWI= 0.5705 x Weight (kg) + 0. 1358 x Height (cm) +0.4575 x Chest an. Right hand diameter (Icm) - 0. 1116 x Iliac diameter (cm.)- 21.037 SE= 1.8)MWII = 0.5572 x Weight (kg.) + 0.1311 x Height (cm.) + i 1.2669 x Right hand diameter (cm.) - 21. 922 (r = 0.9244 SE =1.8)The validity of Oppliger and Tipton's minimal wrestling weight equations wrestlers were checked and none of them were found to be more valid than new regression equations for this group of subjects.

Bu çalışmanın amacı çeşitli nedenlerle kilo ayarlaması yapma durumunda kalan minik Türk güreşçileri için, sağlıklı bir minimal ağırlık teshilinde bulunmak üzere, tahmin denklemi geliştirmekti. Denek güreşçiler, ülkenin çeşitli bölgelerinden Türk Güreş Federasyonu Güreş Eğitim Merkezleri için seçilmiş olan 169 ergenlik öncesi güreşçi adaylarıydı. Tüm gurup üzerinde su altı ağırlık ölçümü, antropometrik çap ve vital kapasite ölçümleri gerçekleştirildi. Minimal ağırlık tespitinde % 5'lik vücut yağ yüzdesi kriteri kabul edildi. Çoklu doğrusal regres- yon İsta ti s ti İd yöntemiyle, vüut çapları kullanılarak geliştirilen denklemler aşağıda sunulmuştur. M Al = 0.5705 (Ağırlık-kg.) + 0.1358 (Boy -cm.) + 0.4575 (göğüs çapı cm) + 1.2793 (sağ çapı-cm) - 0.1116 (İliak çapı -cm.) -21.037 (t-0.927 SH = L8) MHII = 0.5572 (Vücut ağırlığı-kg) + 0.1311 (Bov-cm.) + 0.4384 (Göğüs çapı cm.) + 1,2669 (Sağ el bilek, çapı -cm.) -21.922 (r = 0.9244 SH =1.8) Ayrıca Tipton ve Oppliger tarafından liseli güreşçiler için geliştirilen minimal ağırlık formüllerinin minik Türk güreşçileri için geçerliliği araştırılmış ve denklemlerin doğru taliminde bulunmada uzak ve yetersiz oldukları kanısına varılmıştır.
MİNİK TÜRK GÜREŞÇİLERİ İÇİN MİNİMAL AĞIRLIK TAHMİN DENKLEMİ GELİŞTİRİLMESİ